Smart-Urea-Controlled-Release-Nitrogen-Fertilizer Menggunakan Plastik Biodegradable Poli Asam Laktat Sebagai Carrier - Mujtahid Kaavessina; Chitra Husnabilqis; Meylani Tri Hardiyanti (Program studi Teknik Kimia UNS, 2017)
Poly lactic acid is a polymer that has been developed as an alternative to substitution of conventional polymers. The properties of this polymer are biodegradable in nature and non-toxic substances. These polymers potentially can be used as a matrix for urea carries. The aim of this research was to synthesize poly lactic acid in a low molecular weight. This product can be used as a matrix that urea release controller during the process of fertilization. The methodology consisted of two stages. The first stage was polycondensation of lactic acid and degradability test. Lactic acid was mixed with SnCl2 catalyst 0.1% and heated to 138oC for 24 hours. The second stage was producing in the form of Smart Urea Controlled Release Nitrogen Fertilizer (CRNF). Urea was dissolved in poly lactic acid through a heating process at 150°C to dissolve urea with variation in urea concentration weight of 0.5%; 0.1%; 0.15%; 0.2%; 0.25%; 0.3% and CRNF granulation processes. Finally, the mixture was granulated in ambient temperature. Chemical analysis was done the molecular weight of poly lactic acid. The relationship between intrinsic viscosity and molecular weight was used. The IR spectra (FTIR) was used to fine molecular structure. The release testing of urea from the matrix of poly lactic acid uses UV-VIS Spectrophotometer. The results showed that the average molecular weight of poly lactic acid is 1149.49 g /gmol. FTIR spectra of CRNF with variation in urea concentration weight showed the presence of groups owned by poly lactic acid and urea. The peaks are1627.03 to 1629.92 cm-1 for the -NH group and 3478.77 to 3498.06 cm-1 for group -OH. The existence of these groups proves the existence of urea in CRNF. The release of urea from poly lactic acid occurs by diffusion. It can be seen, when urea in CRNF form immersed in water, the concentration of urea in water increase as well as the increasing immersed time.